A non-invasive study of flow dynamics in membrane distillation hollow fiber modules using low-field nuclear magnetic resonance imaging (MRI) - Fridjonsson, E. O. (2013)
Low-field bench-top nuclear magnetic resonance imaging (MRI) has been applied to investigate the hydrodynamics in novel hollow fiber modules with four different configurations of randomly-packed, spacer-knitted, curly and semi-curly fibers, specifically designed for the membrane distillation (MD) process. Imaging, spatially resolved velocity maps and propagators (probability distributions of displacement/velocity) were all acquired in the modules with flow in the shell side. The MRI data were correlated with overall module performance.